Peranan Informed Consent dalam Pelayanan Kesehatan Sebagai Upaya Preventif Tindak Pidana Malapraktik di Rumah Sakit - Batubara, Sonya A; Manurung, Billy M A; Ginting, Rio F A; Adawiyah, Rodhiatul (JUNCTO: Jurnal Ilmiah Hukum, 2025)
This study aims to examine the legal standing of informed consent in hospitals, to identify the responsibility of hospitals in implementing informed consent, and to explore the role of informed consent in healthcare services as a preventive measure against criminal acts of medical malpractice. The research method employed is juridical normative, which involves the examination of legal norms and jurisprudence related to informed consent, with the objective of evaluating whether these norms are legally effective in preventing malpractice. The study also uses a descriptive approach to gain a better understanding of how informed consent is applied in the actual practice of healthcare services in hospitals. Based on the findings, the author concludes that informed consent, as regulated under Law No. 36 of 2009, should be understood by both patients and medical personnel. The legal framework provides protection for both parties—patients and doctors—and relevant laws are already in place. However, the existing regulations have not yet fully accommodated all operational or practical aspects involved in the implementation of informed consent.